NLRC3 puts the brakes on STING - Mangan, Matthew S.J. (2014)
NOD like receptors (NLRs) areincreasingly implicated in control of pathogen sensing pathways. In this issue of immunity Zhang et al. describe a role for NLRC3 in regulating STING and the inflammatory response to cytosolicDNA.